Hruscsov leváltásának magyarországi visszhangja - Baráth, Magdolna (Acta Scientiarum Socialium, 2014)
The Hungarian Reaction to Nikita Khrushchev’s Replacement Khrushchev’s replacement from the post of the Secretary-General of the Central Committee of the Communist Party of the Soviet Union surprised the Hungarian party leadership with its suddenness and circumstances. It was a considerable loss for János Kádár personally because Khrushchev was his main supporter in the Soviet leadership. Khrushchev’s retirement induced several kinds of rumours about its background and possible consequences. That was the reason why the Hungarian leadership felt it important to give their interpretation of the events and clarify the situation with Moscow. The main quandary was how to accentuate Khrushchev’s merits in the process of de-Stalinization and in the peaceful coexistence with the West, and at the same time demonstrate their loyalty to the new Soviet leadership, which had only been making critical remarks in connection with Khrushchev’s political activity.